Adoption and implementation of balanced scorecard in Malaysia / Tze San Ong ...[et al.] - Tze, San Ong; Boon, Heng Teh; Chee, Kwong Lau; Sharon Lee, Shyan Wong (2010)
This paper reports the results of an empirical study on the adoption and implementation of Balanced Scorecard in Malaysia. More specifically, it investigates the sequential dependency among the four balances Scorecard (BSC) perspectives, namely learning and growth, internal business process, customer value and financial performance. The findings indicate that organizations responded positively to BSC measures and believed the cause and-effect relationship of BSC will lead to improved business efficiency and profitability.